THE INFLUENCE OF SOCIAL MEDIA ON THE DEVELOPMENT OF SLANG AMONG TEENAGERS: A CASE STUDY ON TIKTOK AND INSTAGRAM PLATFORMS - Ratna Rintaningrum; Kartika Nuswantara; Budiawan Budiawan; Erni Hastuti; Rahmi Setiawati (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Social media is part of the digital change that colors the world of communication. The increasingly rapid development brings changes in the language structure adopted from online platforms. The TikTok and Instagram applications that are currently often used by teenagers present an informal language style. This informal language is called slang. Slang is often used by teenagers to simplify language and find identity. However, this often leads to hate speech, violence, and even impoliteness in communication. So this study aims to pay special attention to the challenges posed by slang. Politeness as a necessity must not fade among teenagers. This will also affect acts of violence, hatred and other immoral acts. In this study, researchers used quantitative methods. This is useful for determining the influence of the use of slang among teenagers in communicating. Comparison of views from the questions asked will be the results and discussions. The results of this study in the form of TikTok and Instagram allow teenagers to create and spread new slang quickly. Usage tends to adapt words and phrases according to trends and popular content on this platform. Teenagers who use social media intensively are more likely to use slang in everyday communication. The conclusion of this study is that social media, especially TikTok and Instagram, contribute significantly to the development of slang among teenagers. These platforms accelerate the spread and adoption of new terms, enable language creativity and help build group identity.